Importance of Milk Feeding Pre-weaning to Dairy Calves - Milerky C. Perdomo; José E. P. Santos (EDIS)
Similar to any mammal, newborn dairy calves must consume milk in the first weeks of life because of their inability to properly digest dry feeds. On most dairy farms, milk harvested from cows or reconstituted milk replacer powder provides the primary source of nutrients for calves in the first 4-6 weeks of life before they are able to adequately digest other feeds. This 4-page fact sheet was written by Milerky C. Perdomo and José E.P. Santos, and published by the UF Department of Animal Science, June 2011. (AP photo by Tara Piasio/University of Florida/IFAS)